Lived Experience of Participants of a Korean Medicine-Based Postpartum Program: A Protocol for a Qualitative Research Study. (28th September 2021) - Youn, Inae; Park, Han-Song; Lee, Do-Eun; Suh, Hyo-Weon; Seo, Joohee
Background: The postpartum period is the most critical period in the mother's and child's lives, and integrative medical approaches, including Korean medicine, are preferred for promoting postpartum recovery and managing postpartum symptoms. The socially disadvantaged class is known to be more vulnerable to postpartum depression, obesity, and bleeding, and the National Medical Center is undertaking Korean medicine-based postpartum health management projects for the socially disadvantaged mothers. However, clinical evidence and research data on integrative medicine-based postpartum care to expand the scope of these postpartum programs to help these women are lacking.Aim: To investigate the barriers, benefits, and limitations of integrative medical postpartum health management programs for the socially disadvantaged mothers and investigate the experiences of this population.Methods: A qualitative research methodology is used, and a semi-structured, open-ended interview will be conducted. The interview will be conducted among 10 or fewer participants, with each interview session lasting for 60–120 min. Data will be analyzed using grounded theory framework proposed by Strauss and Corbin.Significance: This study will shed light on the users' experiences and benefits, unmet needs, and limitations of Korean medicine-based postpartum management programs for the socially disadvantaged mothers. The findings will be useful for the improvement of postpartum care programs and used as foundational data for the protocols of quantitative studies in the future.